Formation and characterization of preferred oriented perovskite thin films on single-crystalline substrates. (1st June 2018) - Chen, Lung-Chien; Chen, Cheng-Chiang; Chang, Sheng Hsiung; Lee, Kuan-Lin; Tseng, Zong-Liang; Chen, Sheng-Hui; Kuo, Hao-Chung
Abstract: Three single-crystalline (Al2 O3, GaN/Al2 O3 and InAs) substrates are used to assist the formation of crystallographically preferred oriented CH3 NH3 PbI3 (MAPbI3 ) thin films. The estimation of the lattice mismatch at the MAPbI3 /substrate interface and water-droplet contact angle experiments indicate that the formation of a preferred oriented MAPbI3 thin film is induced by the single-crystalline substrate and is insensitive to the surface wettibility of the substrate. Moreover, the experimental results suggest that the lattice mismatch at the MAPbI3 /single-crystalline semiconductor interface can strongly influence the photovoltaic performance of tandem solar cells.